Silicone adhesive and preparation method thereof
By combining the fast-solid crosslinking agent and the preferred crosslinking curing agent, the existing silicone glue has been solved, and rapid curing and efficient production of silicone glue suitable for photovoltaic modules is achieved.
Patent Information
- Application Number
- CN202310267813.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-20
AI Technical Summary
The existing single-component silicone glue has slow curing and requires high temperature and high humidity curing room, and has low production efficiency; the two-component silicone glue has poor bonding strength and poor water resistance to photovoltaic modules.
The fast solidification crosslinking agent bis-γ-trialkoxy silicon propyl aniline is used to combine with the preferred crosslinking curing agent, and the reaction activity of the entire system is balanced and the curing time is shortened by synergistic action of the preferred components and their dosage ratio. .
It achieves rapid curing, no need for high temperature and high humidity curing, green and energy-saving and environmentally friendly, good bonding strength and good water resistance, and improves the production efficiency of photovoltaic modules.
Smart Images

Figure QLYQS_1 
Figure BDA0004133581040000021 
Figure BDA0004133581040000022
Abstract
Description
Technical Field
[0001] The invention relates to a silicone adhesive and a preparation method thereof, which are applied in the field of organic silicone adhesive production, in particular to the field of organic silicone adhesive production for photovoltaic modules. Background Art
[0002] Photovoltaic modules are affected by external factors such as sunlight, rain, snow, hail, and stable seasonal changes during use. Photovoltaic modules are composed of two pieces of glass (upper glass and lower glass) with EVA film and solar cells as composite layers. The cells are connected in series and parallel by wires to the lead ends, and finally the frame is sealed to form a photovoltaic cell module. This requires that the sealant used in photovoltaic modules not only needs to have good bonding and sealing properties, but also needs to have excellent weather resistance. Liquid room temperature silicone glue has good bonding properties and outstanding weather resistance, and is currently the best material for sealing photovoltaic modules.
[0003] Liquid room temperature silicone adhesive can be divided into two categories: single component and two components according to the product packaging type. Single component liquid silicone adhesive is made by dehydrating polysiloxane and filler at high temperature, and then mixing them with cross-linking agent, coupling agent, catalyst and other additives under moisture-proof conditions and packaging. It is squeezed out of the package when used, and the extruded single component silicone gel is cross-linked and cured from the outside to the inside by contacting moisture in the air. This silicone adhesive has the advantages of easy use and low equipment investment. It has become a commonly used sealant for bonding photovoltaic module frames and junction boxes. Single component room temperature silicone adhesive relies on absorbing moisture in the environment to cure. It has the characteristic of curing from the outside to the inside, which leads to a slow increase in strength and a long handling and packing cycle. It requires a special humidification and heating curing room, and the production efficiency is difficult to meet the increasing market demand.
[0004] Two-component silicone adhesive is a two-component silicone adhesive that is packaged separately from the base material and the vulcanizing agent. When used, the two components are mixed evenly in a certain proportion before use. Compared with single-component room temperature silicone adhesive, two-component silicone adhesive has lower requirements for the temperature and humidity of the curing environment, fast deep curing speed, and can achieve synchronous curing of the inside and outside, which can greatly shorten the handling and packaging time. However, the existing two-component silicone adhesive has the disadvantages of poor bonding strength to photovoltaic modules and poor water resistance.
[0005] For example, patent CN201710153476.2 discloses a high-performance silicone sealant for photovoltaic modules and a preparation method thereof. The invention provides a one-component de-oxime silicone sealant. The silicone sealant has good comprehensive performance and can extend the service life of solar products. It does not solve the problem that the single-component silicone sealant cures slowly and requires a long curing time in the curing room. Patent CN201810889728.2 discloses a fast-curing silicone sealant for photovoltaic modules and a preparation method thereof. The invention is composed of alkoxy-terminated polydimethylsiloxane, polydimethylsiloxane, filler, cross-linking agent, coupling agent and first catalyst chelate titanate catalyst. It can be applied to a variety of adhesive materials and has excellent bonding strength. Fast-curing single-component silicone dealcohol sealant for photovoltaic modules. According to its embodiment data, the 24-hour curing depth is 4.0 mm, which is higher than the internal curing speed of ordinary single-component. It also requires a curing room and cannot be quickly transported and packed. Patent CN202011428425.4 discloses a silicone encapsulation material for photovoltaic modules and a preparation method thereof. The invention includes two components, A and B, which are mainly composed of phenyl vinyl silicone oil and phenyl vinyl silicone resin. It is an addition-type two-component transparent silicone adhesive with excellent mildew resistance and good light transmittance. The patent requires high-temperature curing at 130°C, which is quite different from the room temperature curing of the present invention. Patent CN202111559998.5 discloses a fast-curing two-component silicone structural adhesive and a preparation method thereof. The fast-curing two-component silicone structural adhesive includes components A and B; component A includes room temperature vulcanized silicone rubber, inorganic filler, and synergist; component B includes methyl silicone oil, carbon black, ethyl silicate, organic tin catalyst, coupling agent, and glycine iron; the patent is mainly used for structural adhesives, and its bonding strength is low and has no advantages over the present invention, and there is no mention of water resistance to UV and double 85 performance (i.e., water resistance).
[0006] Therefore, it has become an urgent task to provide a silicone adhesive and its preparation method which can cure quickly, effectively improve the production efficiency of photovoltaic modules, does not require a high temperature and high humidity curing room, is energy-saving and environmentally friendly, and has good water resistance. Summary of the invention
[0007] In order to overcome the shortcomings of existing single-component silicone adhesives such as slow curing, the need for a curing room, and the inability to quickly transport and pack, and the shortcomings of two-component silicone adhesives such as poor bonding strength to photovoltaic modules and poor water resistance, the present invention provides a silicone adhesive and a preparation method thereof. By adopting a fast-curing cross-linking agent, bis-trialkoxysilylpropylaniline, in combination with a cross-linking curing agent prepared from preferred components, as well as the synergistic effect of the preferred components in the system and their dosage ratios, the reaction activity of the entire system is balanced, the curing time is shortened, no separate curing time is required, continuous production can be achieved, no high-temperature and high-humidity curing room is required, green, energy-saving and environmentally friendly, and the adhesive strength is good and the water resistance is good.
[0008] The technical solution of the present invention is as follows:
[0009] A silicone adhesive is prepared by mixing component A and component B in a volume ratio of 1:0.9-1.1 when used:
[0010] The A component is mainly prepared from the following components in the following weight ratios:
[0011]
[0012] The B component is mainly prepared from the following components in the following weight ratios:
[0013]
[0014]
[0015] Wherein, the fast-curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline;
[0016] The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 2-5:8-15:70-80.
[0017] The silicone adhesive of the present application balances the reaction activity of the entire system and shortens the curing time by adopting the preferred fast-curing cross-linking agent bis-trialkoxysilylpropylaniline in combination with the cross-linking curing agent prepared from the preferred components, as well as the synergistic effect of the preferred components in the system and their dosage ratios. It does not require a separate curing time, can achieve continuous production, does not require a high-temperature and high-humidity curing room, and is green, energy-saving and environmentally friendly. The silicone adhesive is composed of two components. The preferred fast-curing crosslinking agent bis-trialkoxysilylpropylaniline in the system is different from traditional crosslinking agents (such as methyltrimethoxysilane, methyl orthosilicate, ethyl orthosilicate, vinyltriethoxysilane and methyltriethoxysilane, etc.) in that: 1. Each molecule has six methoxy reactive groups, which is twice as many as ordinary silane; 2. The crosslinking agent itself contains aniline groups, which can self-catalyze and further enhance the reaction activity, and can be matched with a crosslinking curing agent prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a preferred ratio. The high-activity curing agent and the low-activity curing agent can balance the reaction activity of the entire system, shorten the curing time, and will not cause excessive local reaction to form gel, so it can provide better crosslinking density and activity, shorten the curing time to less than 15 minutes, and no separate curing time is required, continuous production can be achieved, and the bonding strength and water resistance are good. Compared with traditional one-component adhesive for photovoltaic modules, it can be cured quickly at room temperature and can be transported after 4-6 hours. There is no need to match special high-temperature and high-humidity curing rooms for photovoltaic modules, which can effectively reduce energy consumption and improve production efficiency. Compared with existing two-component silicone adhesives, it has better bonding strength and water resistance. Among them, silane coupling agents can improve the adhesion between silicone adhesive and photovoltaic module substrates. The terminal hydroxyl polybutadiene main chain is directly connected to the carbon-carbon structure, which has good hydrophobicity and hydrolysis resistance. In addition, the terminal hydroxyl group will cross-link the alkoxy cross-linking reaction in the cross-linking agent, and has good compatibility with the system, so that the silicone adhesive can withstand long-term rain erosion and corrosion, and increase the water resistance of the product. Nano calcium carbonate is one of the main fillers of silicone, which can play a reinforcing and thixotropic role. Carbon black is thickening and coloring. Waterproof filler: As a reinforcing filler, it increases the mechanical properties of the product. The viscosity of the α,ω-dihydroxy polydimethylsiloxane in the component a and component b systems at 25°C is 5000-200000 mPa·s, and the viscosity of the polydimethylsilicone in the component A and component B systems at 25°C is 50-1000 mPa·s. The viscosity of the hydroxy-terminated polydibutylene at 25°C is 5000-80000 mPa·s.
[0018] The bis-γ-trialkoxysilylpropylaniline is prepared by mixing chloropropyltrialkoxysilane and aniline in a molar ratio of 1.8-2.2:1.
[0019] Bis-γ-trialkoxysilylpropylaniline contains six reactive alkoxy groups, which can increase the crosslinking density and reactivity of silicone adhesive and enhance the bonding strength. At the same time, the phenyl group can also enhance the heat resistance.
[0020] The nano calcium carbonate is nano calcium carbonate surface treated with a silane coupling agent or stearic acid, has a moisture content of ≤0.3%, and has a particle size of 0.1-20 μm or any combination of any two or more particle sizes.
[0021] Nano calcium carbonate surface treated with silane coupling agent or stearic acid has better compatibility in the system and can provide better thixotropy and reinforcement of the colloid.
[0022] The waterproof filler is one of mica powder and talcum powder or any combination of the two, and the particle size of the waterproof filler is one of 0.1-200 μm or any combination of any two or more particle sizes.
[0023] In the present case, long carbon chain reactive liquid rubber-terminated hydroxyl polybutadiene with good hydrophobicity and preferred flaky waterproof fillers mica powder and talcum powder are added to the system, which can form a special network structure in the system, effectively blocking water vapor from penetrating into the interior of the colloid, preventing damage to the internal structure of the colloid and the bonding effect between the silicone glue and the substrate, so that the water resistance of the silicone glue can be improved without adding other special additives to the system.
[0024] The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 3-6:1-2:1-2.
[0025] The use of three preferred coupling agents can improve the situation that a single silane coupling agent does not stick to certain substrates, expand the scope of application of bonding and greatly improve the bonding effect. Among them, the bisaminosilane oligomer can be Jiangxi Chenguang New Material CG-1146, which has good adhesion to the back sheet of photovoltaic modules.
[0026] The catalyst is one of dibutyltin dilaurate, dibutyltin dioctoate, dibutyltin diacetate, stannous octoate, n-butyl titanate or tetraisopropyl titanate, or any combination of any two or more thereof.
[0027] The preferred catalyst is more common and catalytically stable.
[0028] The molecular formula of the bis-γ-trialkoxysilylpropylaniline is:
[0029]
[0030] Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof.
[0031] The preparation method of the silicone adhesive mainly comprises the following steps performed in sequence:
[0032] (1) Preparation of component A
[0033] Start the stirrer and adjust the stirring speed to 300-400 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.06-0.09 MPa, and mix evenly to obtain the A component;
[0034] (2) Preparation of component B
[0035] ① Start the mixer and adjust the stirring speed to 300-400 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxy polydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 100-150 minutes at 120-130°C and vacuum degree of 0.06-0.09MPa to remove moisture.
[0036] ② Cool the mixture obtained in step ① to 23-25° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 30-60 minutes to obtain component B.
[0037] The preparation method of the silicone adhesive components A and B of the present application has simple steps and is easy to operate.
[0038] The preparation method of the fast-curing crosslinking agent mainly comprises the following steps performed in sequence:
[0039] ① Start the stirrer and adjust the stirring speed to 30-50 rpm. First, put aniline into the stirrer. Then, under nitrogen protection, drop chloropropyltrialkoxysilane into the aniline and control the addition to be completed within 2-3 hours.
[0040] ② Then, the stirring speed is maintained and the mixture is kept at 60-80° C. for 3-4 hours to react, thereby obtaining the fast-curing crosslinking agent.
[0041] The preparation method of the fast-curing cross-linking agent has simple steps and is easy to operate.
[0042] The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: mixing component A and component B in a volume ratio of 1:0.9-1.1 under a vacuum degree of 0.06-0.09 MPa to obtain the silicone adhesive.
[0043] The silicone adhesive of the present application only needs to be simply mixed with component A and component B when used, and is convenient to use. Preferably, a vacuum degassing machine can be used when mixing component A and component B.
[0044] Compared with the prior art, the present invention has the following advantages:
[0045] 1) The silicone adhesive of the present application balances the reaction activity of the entire system, shortens the curing time, does not require a separate curing time, can achieve continuous production, does not require a high-temperature and high-humidity curing room, is green, energy-saving and environmentally friendly, and has good bonding strength and water resistance by using a fast-curing crosslinking agent bis-trialkoxysilylpropylaniline and a crosslinking curing agent prepared from preferred components, as well as the synergistic effect of the preferred components in the system and their usage ratios;
[0046] 2) The silane coupling agent is a mixture of aminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a preferred ratio. The three coupling agents are used together to improve the situation that a single coupling agent is not sticky to individual substrates, expand the application range of bonding and greatly improve the bonding effect;
[0047] 3) Nano calcium carbonate surface treated with silane coupling agent or stearic acid has better compatibility in the system, providing better thixotropy and reinforcement of the colloid;
[0048] 4) The preparation method of the silicone adhesive has simple steps and is easy to operate. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is described in detail below in conjunction with the embodiments of the specification.
[0050] Example 1
[0051] The silicone adhesive of the present invention is prepared by mixing component A and component B in a volume ratio of 1:1 when used:
[0052] The A component is mainly prepared from the following components in the following weight ratios:
[0053]
[0054] The B component is mainly prepared from the following components in the following weight ratios:
[0055]
[0056] Wherein, the fast curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline, and its molecular formula is:
[0057]
[0058] Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof;
[0059] The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 5:15:80.
[0060] The bis-γ-trialkoxysilylpropylaniline is prepared by mixing chloropropyltrialkoxysilane and aniline in a molar ratio of 2:1.
[0061] The nano calcium carbonate is nano calcium carbonate surface-treated with stearic acid, and the water content of the nano calcium carbonate is 0.3% and the particle size is 8 μm.
[0062] The waterproof filler is mica powder, and the particle size of the waterproof filler is 80 μm.
[0063] The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 6:2:2.
[0064] The catalyst is dibutyltin dilaurate.
[0065] The preparation method of the silicone adhesive mainly comprises the following steps performed in sequence:
[0066] (1) Preparation of component A
[0067] Start the stirrer and adjust the stirring speed to 350 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.08 MPa, and mix evenly to obtain the A component;
[0068] (2) Preparation of component B
[0069] ① Start the mixer and adjust the stirring speed to 350 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxypolydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 120 minutes at 120-130°C and vacuum degree of 0.08MPa to remove moisture.
[0070] ② Cool the mixture obtained in step ① to 24° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 40 minutes to obtain component B.
[0071] The preparation method of the fast-curing crosslinking agent mainly comprises the following steps performed in sequence:
[0072] ① Start the stirrer and adjust the stirring speed to 40 rpm. First, put aniline into the stirrer. Then, under nitrogen protection, drop chloropropyltrialkoxysilane into the aniline and control the addition to be completed within 2.5 hours.
[0073] ② Then, the stirring speed was maintained and the mixture was kept at 70° C. for 3.5 hours to react, thereby obtaining the fast-curing crosslinking agent.
[0074] The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: mixing component A and component B in a volume ratio of 1:1 under a vacuum degree of 0.08 MPa to obtain the silicone adhesive.
[0075] Example 2
[0076] The silicone adhesive of the present invention is prepared by mixing component A and component B in a volume ratio of 1:0.9 when used:
[0077] The A component is mainly prepared from the following components in the following weight ratios:
[0078]
[0079] The B component is mainly prepared from the following components in the following weight ratios:
[0080]
[0081]
[0082] Wherein, the fast curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline, and its molecular formula is:
[0083]
[0084] Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof;
[0085] The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 2:8:70.
[0086] The bis-γ-trialkoxysilylpropylaniline is prepared by mixing chloropropyltrialkoxysilane and aniline in a molar ratio of 1.8:1.
[0087] The nano calcium carbonate is nano calcium carbonate surface-treated with stearic acid, and the water content of the nano calcium carbonate is 0.1% and the particle size is 0.1 μm.
[0088] The waterproof filler is mica powder or talcum powder or any combination of the two, and the particle size of the waterproof filler is 200 μm.
[0089] The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 5:1:1.5.
[0090] The catalyst is any combination of dibutyltin diacetate and stannous octoate.
[0091] The preparation method of the silicone adhesive mainly comprises the following steps performed in sequence:
[0092] (1) Preparation of component A
[0093] Start the stirrer and adjust the stirring speed to 300 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.09 MPa, and mix evenly to obtain the A component;
[0094] (2) Preparation of component B
[0095] ① Start the mixer and adjust the stirring speed to 300 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxypolydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 150 minutes at 130°C and vacuum degree of 0.06MPa to remove moisture.
[0096] ② Cool the mixture obtained in step ① to 23° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 60 minutes to obtain component B.
[0097] The preparation method of the fast-curing crosslinking agent mainly comprises the following steps performed in sequence:
[0098] ① Start the stirrer and adjust the stirring speed to 30 rpm. First, put aniline into the stirrer. Then, under nitrogen protection, drop chloropropyltrialkoxysilane into the aniline and control the addition to be completed within 3 hours.
[0099] ② Then, the stirring speed is maintained and the mixture is kept at 60° C. for 4 hours to react, thereby obtaining the fast-curing crosslinking agent.
[0100] The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: mixing component A and component B in a volume ratio of 1:0.9 under a vacuum degree of 0.06 MPa to obtain the silicone adhesive.
[0101] Example 3
[0102] The silicone adhesive of the present invention is prepared by mixing component A and component B in a volume ratio of 1:1.1 when used. Component A is mainly prepared by the following components in the following weight ratios:
[0103]
[0104] The B component is mainly prepared from the following components in the following weight ratios:
[0105]
[0106] Wherein, the fast curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline, and its molecular formula is:
[0107]
[0108] Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof;
[0109] The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 4:10:75.
[0110] The bis-γ-trialkoxysilylpropylaniline is prepared by mixing chloropropyltrialkoxysilane and aniline in a molar ratio of 2.2:1.
[0111] The nano calcium carbonate is nano calcium carbonate that has been surface treated with a silane coupling agent, and the water content of the nano calcium carbonate is 0.2% and the particle size is 20 μm.
[0112] The waterproof filler is mica powder or talcum powder or any combination of the two, and the particle size of the waterproof filler is 0.1 μm.
[0113] The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 3:1.5:1.
[0114] The catalyst is one of dibutyltin dilaurate, dibutyltin dioctoate, dibutyltin diacetate, stannous octoate, n-butyl titanate or tetraisopropyl titanate, or any combination of any two or more thereof.
[0115] The preparation method of the silicone adhesive mainly comprises the following steps performed in sequence:
[0116] (1) Preparation of component A
[0117] Start the stirrer and adjust the stirring speed to 400 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.06 MPa, and mix evenly to obtain the A component;
[0118] (2) Preparation of component B
[0119] ① Start the mixer and adjust the stirring speed to 400 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxypolydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 100 minutes at 120°C and vacuum degree of 0.09 MPa to remove moisture.
[0120] ② Cool the mixture obtained in step ① to 25° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 30 minutes to obtain component B.
[0121] The preparation method of the fast-curing crosslinking agent mainly comprises the following steps performed in sequence:
[0122] ① Start the stirrer and adjust the stirring speed to 50 rpm. First, put aniline into the stirrer. Then, under nitrogen protection, drop chloropropyltrialkoxysilane into the aniline and control the addition to be completed within 2 hours.
[0123] ② Then, the stirring speed is maintained and the mixture is kept at 80° C. for 3 hours to react, thereby obtaining the fast-curing crosslinking agent.
[0124] The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: under a vacuum degree of 0.09 MPa, mixing component A and component B in a volume ratio of 1:1.1 to obtain the silicone adhesive.
[0125] Example 4
[0126] The silicone adhesive of the present invention is prepared by mixing component A and component B in a volume ratio of 1:1 when used:
[0127] The A component is mainly prepared from the following components in the following weight ratios:
[0128]
[0129] The B component is mainly prepared from the following components in the following weight ratios:
[0130]
[0131] Wherein, the fast curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline, and its molecular formula is:
[0132]
[0133] Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof;
[0134] The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 5:10:70.
[0135] The nano calcium carbonate is nano calcium carbonate surface-treated with a silane coupling agent, and the water content of the nano calcium carbonate is 0.1%, and the particle size is any combination of 0.1 μm and 20 μm.
[0136] The waterproof filler is any combination of mica powder or talcum powder, and the particle size of the waterproof filler is any combination of 0.1 μm and 200 μm.
[0137] The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 4:2:2.
[0138] The catalyst is dibutyltin dioctoate.
[0139] The preparation method of the silicone adhesive mainly comprises the following steps performed in sequence:
[0140] (1) Preparation of component A
[0141] Start the stirrer and adjust the stirring speed to 350 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.07 MPa, and mix evenly to obtain the A component;
[0142] (2) Preparation of component B
[0143] ① Start the mixer and adjust the stirring speed to 350 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxypolydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 120 minutes at 125°C and vacuum degree of 0.08MPa to remove moisture.
[0144] ② Cool the mixture obtained in step ① to 24° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 35 minutes to obtain component B.
[0145] The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: mixing component A and component B in a volume ratio of 1:1 under a vacuum degree of 0.07 MPa to obtain the silicone adhesive.
[0146] Manufacturer information:
[0147] Bisaminosilane oligomer: Jiangxi Chenguang New Materials Co., Ltd. CG-1146
[0148] Aminopropyltriethoxysilane: Jiangxi Chenguang New Materials Co., Ltd. KH-550
[0149] Aminoethylaminopropyltrimethoxysilane: Jiangxi Chenguang New Materials Co., Ltd. KH-792
[0150] Methyltrimethoxysilane: Hubei New Blue Sky New Materials Co., Ltd. D-20
[0151] Ethyl orthosilicate: Hubei New Blue Sky New Materials Co., Ltd. D-130
[0152] Polymethyltriethoxysilane: Hubei New Blue Sky New Materials Co., Ltd. D-23
[0153] Nano calcium carbonate: SP200 from Shanxi Lanhua Huaming Nanomaterials Co., Ltd.
[0154] α,ω-Dihydroxypolydimethylsiloxane: Room temperature vulcanized methyl silicone rubber (107) of Hesheng Silicon Industry Co., Ltd.
[0155] Polydimethylsilicone oil: Hesheng Silicone Industry Co., Ltd. Methyl silicone oil (201)
[0156] Hydroxyl-terminated polydibutylene: Polybd R-45HT from Idemitsu Petrochemical Co., Ltd.
[0157] Carbon black: Cabot (China) Investment Co., Ltd. M570
[0158] Experimental data:
[0159] Comparison sample:
[0160] Comparative sample 1: A single-component deoxime-type sealant product for solar panels according to Example 2 of Publication No. CN103305181A was used.
[0161] Comparative sample 2: The fast-curing two-component silicone structural adhesive product of Example 3 of publication number CN114262599A is used. Testing method:
[0162] Tensile strength and elongation at break: tested in accordance with the requirements of GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";
[0163] Tensile strength and elongation at break (double 85): According to the provisions of IEC61215 "Crystalline silicon photovoltaic modules for terrestrial use - Scope of application for design identification and finalization", the tensile strength and elongation of the product are measured after aging for 1000 hours at a temperature of 85°C and a humidity of 85%;
[0164] Tensile strength and elongation at break (water UV): Tested in accordance with the provisions of 5.12 of JC / T485-2007 "Elastic Sealant for Building Windows", the immersion time is 1000h, and the surface temperature of the specimen during the illumination period is (40±5)℃;
[0165] Shear strength: Test the product according to the requirements of GB / T 7214-2008 "Determination of tensile shear strength of adhesives";
[0166] Surface drying time: Determined according to GB / T13477.5-2002 "Test methods for building sealing materials" (5) Surface drying time;
[0167] Curing time: The time required for the sealant to fully cure.
[0168] Table 1 Test results of silicone adhesive performance in various embodiments
[0169]
[0170]
[0171] As can be seen from the table above, the products of Examples 1-4 have a fast curing time of only 4-5 hours and excellent water resistance, while Comparative Example 1 is a single-component deoxime sealant product, which takes 48 hours (2 days) to cure and requires a special photovoltaic module high temperature and high humidity curing room, which has a long production cycle. Compared with the single-component silicone adhesive product of Comparative Example 2, the product of this case has better bonding strength and good water resistance.
[0172] The silicone adhesive and the preparation method thereof described in the present invention are not limited to the above-mentioned embodiments. Any improvement or replacement based on the principle of the present invention should be within the protection scope of the present invention.
Claims
1. A silicone adhesive, characterized in that: The silicone adhesive is prepared by mixing component A and component B in a volume ratio of 1:0.9-1.1 when used: The A component is mainly prepared from the following components in the following parts by weight: α,ω-dihydroxy polydimethylsiloxane 90-110 parts 5-10 parts of hydroxyl-terminated polybutadiene 10-20 parts of polydimethylsilicone oil 80-100 parts of nano calcium carbonate; The B component is mainly prepared from the following components in the following parts by weight: Polydimethylsilicone oil 90-110 parts α,ω-dihydroxy polydimethylsiloxane 20-50 parts Waterproof filler 20-40 parts Carbon black 30-40 parts 2-5 parts of fast curing crosslinking agent 80-100 parts of cross-linking curing agent Silane coupling agent 5-10 parts Catalyst 0.5-2 parts; Wherein, the fast-curing crosslinking agent is bis-γ-trialkoxysilylpropylaniline; The cross-linking curing agent is prepared by mixing methyltrimethoxysilane, ethyl orthosilicate and polymethyltriethoxysilane in a mass ratio of 2-5:8-15:70-80; The molecular formula of the bis-γ-trialkoxysilylpropylaniline is: Wherein, R1 is an alkoxy group, and the alkoxy group is one of methoxy, ethoxy or propoxy or any combination of any two or more thereof.
2. The silicone adhesive according to claim 1, characterized in that: The bis-γ-trialkoxysilylpropylaniline is prepared by mixing chloropropyltrialkoxysilane and aniline in a molar ratio of 1.8-2.2:
1.
3. The silicone adhesive according to claim 1, characterized in that: The nano calcium carbonate is nano calcium carbonate surface treated with a silane coupling agent or stearic acid, and the water content of the nano calcium carbonate is ≤0.3%, and the particle size is one of 0.1-20 μm or any combination of any two or more particle sizes.
4. The silicone adhesive according to claim 1, characterized in that: The waterproof filler is one of mica powder and talcum powder or any combination of the two, and the particle size of the waterproof filler is one of 0.1-200 μm or any combination of any two or more particle sizes.
5. The silicone adhesive according to claim 1, characterized in that: The silane coupling agent is prepared by mixing bisaminosilane oligomer, aminopropyltriethoxysilane and aminoethylaminopropyltrimethoxysilane in a mass ratio of 3-6:1-2:1-2.
6. The silicone adhesive according to claim 1, characterized in that: The catalyst is one of dibutyltin dilaurate, dibutyltin dioctoate, dibutyltin diacetate, stannous octoate, n-butyl titanate or tetraisopropyl titanate, or any combination of any two or more thereof.
7. The method for preparing silicone adhesive according to any one of claims 1 to 6, characterized in that: It mainly includes the following steps in order: (1) Preparation of component A Start the stirrer and adjust the stirring speed to 300-400 rpm, then add the α,ω-dihydroxy polydimethylsiloxane, terminal hydroxy polybutadiene, polydimethylsilicone oil and nano calcium carbonate in the A component system into the stirrer, control the vacuum degree to 0.06-0.09 MPa, and mix evenly to obtain the A component; (2) Preparation of component B ① Start the mixer and adjust the stirring speed to 300-400 rpm. Then add the polydimethylsilicone oil, α,ω-dihydroxy polydimethylsiloxane, waterproof filler and carbon black in the B component system into the mixer. Stir for 100-150 minutes at 120-130°C and vacuum degree of 0.06-0.09MPa to remove moisture. ② Cool the mixture obtained in step ① to 23-25° C., then maintain the stirring speed, add the fast-curing crosslinking agent, crosslinking curing agent, silane coupling agent and catalyst into the mixer and mix with the mixture, and stir for 30-60 minutes to obtain component B.
8. The method for preparing silicone adhesive according to claim 7, characterized in that: The preparation method of the fast-curing crosslinking agent mainly comprises the following steps performed in sequence: ① Start the stirrer and adjust the stirring speed to 30-50 rpm. First, put aniline into the stirrer. Then, under nitrogen protection, drop chloropropyltrialkoxysilane into the aniline and control the addition to be completed within 2-3 hours. ② Then, the stirring speed is maintained and the mixture is kept at 60-80° C. for 3-4 hours to react, thereby obtaining the fast-curing crosslinking agent.
9. The method for preparing silicone adhesive according to claim 7, characterized in that: The method for preparing the silicone adhesive further comprises step (3) of preparing the silicone adhesive: mixing component A and component B in a volume ratio of 1:0.9-1.1 under a vacuum degree of 0.06-0.09 MPa to obtain the silicone adhesive.
Citation Information
Patent Citations
Single-component deoximation type sealing adhesive for solar module
CN103305181A
Organic silicon sealing glue for high-performance photovoltaic assembly, and preparation method thereof
CN108624281A
A fast-curing silicone sealant for photovoltaic modules and its preparation method
CN109181623B
A silicone encapsulation material for photovoltaic modules and its preparation method
CN112538334B
Rapidly-cured two-component silicone structural adhesive and preparation method thereof
CN114262599A